2008
DOI: 10.1007/s00270-007-9267-3
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Management of Acute Bleeding Arterioenteric Fistulas

Abstract: The objective of this study was to review the outcome of endovascular transcatheter repair of emergent arterioenteric fistulas. Cases of abdominal arterioenteric fistulas (defined as a fistula between a major artery and the small intestine or colon, thus not the esophagus or stomach), diagnosed over the 3-year period between December 2002 and December 2005 at our institution, were retrospectively reviewed. Five patients with severe enteric bleeding underwent angiography and endovascular repair. Four presented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 29 publications
0
29
0
3
Order By: Relevance
“…Other negative predictive factors include older age, cirrhosis, oncologic diseases, multiple organ failure, and current corticosteroid treatment [7,56]. Generally, the morbidity and mortality associated with endovascular intervention is lower or comparable than for surgical procedure [28,42,[57][58][59].…”
Section: Outcomementioning
confidence: 99%
See 1 more Smart Citation
“…Other negative predictive factors include older age, cirrhosis, oncologic diseases, multiple organ failure, and current corticosteroid treatment [7,56]. Generally, the morbidity and mortality associated with endovascular intervention is lower or comparable than for surgical procedure [28,42,[57][58][59].…”
Section: Outcomementioning
confidence: 99%
“…The most frequent etiology is diverticulosis and less frequent is bleeding in angiodysplasia, tumors, inflammatory disease, and bleeding from Meckel's diverticulum [4,5]. A separate group comprises hemorrhage from sources outside the digestive tract, such as the biliary tract, the pancreatic duct, and arterioenteric fistula, or visceral arteries aneurysms or pseudoaneurysms [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Intravascular balloon occlusion would be an effective first step management to control massive bleeding from arterial fistula 6) . However, interventional balloon occlusion and insertion of covered stent are possible only in about 100 hospitals which are about 10% of clinics performing lumbar disc surgery in South Korea according to the data from Health Insurance Review and Assessment Service of Korea.…”
Section: Discussionmentioning
confidence: 99%
“…Early recognition of herald bleeding and urgent surgical intervention is essential to decrease the mortality rate of AEF. Some authors suggested to place an occlusive balloon at, or above, the level of the AEF, in order to gain time to consider different therapeutic options and even to transport the patient within the institution when needed (Leonhardt et al, 2008). Treatment typically entails removal of the graft and any infected tissue, revascularization, and closure of the bowel fistula.…”
Section: Discussionmentioning
confidence: 99%